Azo polymers with electronical push and pull structures prepared via RAFT polymerization and its photoinduced birefringence behavior (eXPRESS Polymer Letters)
Two methacrylate monomers containing azo and electronical push and pull structure, e.g. 2-Methyl-acrylic-acid-2-{[4-(4-cyano-phenylazo)-3-methyl-phenyl]-ethyl-amino-ethyl ester (MACP) with cyano substituted and 2-Methylacrylic-acid-2-{ethyl-[4-(4-methoxy-phenylazo)-3-methyl-phenyl]-amino}-ethyl ester (MAMP) with methoxy substituted, were synthesized and polymerized using 2-cyanoprop-2-yl dithiobenzoate (CPDB) as chain transfer agent and 2,2'-azobisisobutyronitrile (AIBN) as initiator. The results showed that the polymerization displayed characteristics of ‘living’/controlled free radical polymerization. Thus, the obtained polymers, polyMACP (pMACP) and polyMAMP (pMAMP), had controlled molecular weights and narrow molecular weights distribution. The chain extension experiments of pMACP and pMAMP using styrene as the second monomer were successfully carried out. The photo-induced trans-cis-trans isomerization kinetic of pMACP and pMAMP in chloroform solution were described. Marked differences in rate for the trans-cis and cis-trans isomerization of pMACP and pMAMP were observed in chloroform solution due to the different electronic effects in these two polymers. Photoinduced birefringence and surface relief grating (SRG) of the pMACP and pMAMP were investigated in thin film state.